Prestasi Belajar Matematika Ditinjau dari Kepercayaan Diri dan Keaktifan Siswa di Kelas - Maman Achdiyat; Kartika Dian Lestari (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2016)
. The purpose of the study was to analyze whether there is influence confidence and activity of students in the class of the mathematics achievement class VIII SMP Negeri 208 Jakarta. The research method in this study is a survey method through correlation techniques. The population in this study were all students of class VIII SMP 208. Sampling techniques using random sampling techniques,. The amount of a sample group of 40 students. Confidence data collection instruments, and active participation by students in class with each of 30 questionnaires and data collection Mathematics Learning Achievement through documents UAS value. Then test data requirements that normality test with chi-square test, which marks the third data Xh <Xt, namely Confidence (5.65 <7.815), active participation by students in Grades (1.42 <7.815), mathematics Learning Achievement (0, 39 <7.815), then three normal distribution. The next test of linearity regression with ? = 0.05. Mathematics Learning Achievement on Self Confidence Fh <Ft (1.015 <2.35), then H0 is accepted concluded subsequent linear regression model patterned Mathematics Learning Achievement of the activeness of students in Grades Fh <Ft (0.4753 <2.13) H0 accepted, patterned linear regression model. Hypothesis testing technique used is the technique of double correlation. Double correlation test with ? = 0.05, then to DK1 = 2 and obtained Ftabel dk2 = 37 = 3.25. Because Fh> Ft (6.87 <3.25) is high, we conclude that together a significant difference between Confidence and active participation by students in Grades towards mathematics achievement Keywords: Confidence, liveliness Students in Classroom, Learning Achievement in Mathematics.